2023
DOI: 10.32628/ijsrset2310148
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Mechanical Properties of Aluminium - Boron carbide Composites

Abstract: In this investigation, metal-matrix composites of Aluminium matrix reinforced with boron carbide (B4C) particles were fabricated by stir casting technique. Aluminium is selected as the matrix material and boron carbide as reinforced particles are mixed in different weight percentages (0, 2.5, 5 and 7.5 wt %). The test samples were prepared as per ASTM standards to investigate mechanical properties. The experimental result reveals that the tensile strength and hardness increases with the increase in B4C percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The result shows that the hardness of the composites is higher than the unreinforced matrix metal and the hardness of the composites increases linearly with increasing the weight percentage of ZrB2. R. Arunkumar [8] concluded that the increment in the weight percentage of the reinforcement increases the hardness of the composites. The mechanical and wear properties of aluminum based composites reinforced with zirconia were investigated by G. Karthikeyan and G.R.Jinu [14].…”
Section: Figure-2: Percentage Elongation Of Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The result shows that the hardness of the composites is higher than the unreinforced matrix metal and the hardness of the composites increases linearly with increasing the weight percentage of ZrB2. R. Arunkumar [8] concluded that the increment in the weight percentage of the reinforcement increases the hardness of the composites. The mechanical and wear properties of aluminum based composites reinforced with zirconia were investigated by G. Karthikeyan and G.R.Jinu [14].…”
Section: Figure-2: Percentage Elongation Of Compositesmentioning
confidence: 99%
“…The lowest tensile strength is obtained for aluminium alloy (Al6061) is 97.2 MPa and highest tensile strength is obtained for Al6061-7.5%TiC is 151.3 MPa raised by about 54.1MPa (55.6%) compare as cast base alloy. R. Arunkumar[8] have used aluminium 7050 as the matrix material and boron carbide with weight percentage (0, 2.5, 5 and 7.5) as the reinforcement to produce the composite by stir casting technique. The test samples were prepared as per ASTM standards to investigate mechanical properties.…”
mentioning
confidence: 99%
“…Among these routes stir casting technique is an only method to produce AMCs with proper enhanced strength because of simple and economical process, enormous production, and difficult parts also makes easier, limited wettability of reinforcement [19][20][21]. Arunkumar et al [22] studied the mechanical properties on stir casted LM24 with their reinforcement of aluminium oxide, mica and graphite at various weight percentages. It is revealed that the mica and aluminium oxide improves the hardness strength and ductility.…”
Section: Introductionmentioning
confidence: 99%